2018
DOI: 10.1016/j.tcs.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Contraction and deletion blockers for perfect graphs and H-free graphs

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…When k and d are fixed instead of being part of the input, we denote the corresponding problem by k-Contraction(π, d). Blocker problems with the edge contraction operation have already been studied with respect to the chromatic number, clique number, and independence number [16,32], and the domination number [21,22], denoted by χ, ω, α, and γ, respectively. These works address the problem from the point of view of graph classes.…”
Section: Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…When k and d are fixed instead of being part of the input, we denote the corresponding problem by k-Contraction(π, d). Blocker problems with the edge contraction operation have already been studied with respect to the chromatic number, clique number, and independence number [16,32], and the domination number [21,22], denoted by χ, ω, α, and γ, respectively. These works address the problem from the point of view of graph classes.…”
Section: Questionmentioning
confidence: 99%
“…These works address the problem from the point of view of graph classes. Diner et al [16] showed, among other results, that Contraction(π) is NP-complete restricted 64:3 to split graphs for π ∈ {χ, α, ω}, but it is polynomial-time solvable in this graph class for fixed d in all three cases. Galby et al [21,22] recently initiated the study of the problem for π = γ for the case d = 1, providing several negative and positive results restricted to particular graph classes, such as a polynomial-time algorithm for k-Contraction(γ, 1) on (P 5 + pK 1 )-free graphs, for any p ≥ 1.…”
Section: Questionmentioning
confidence: 99%
“…. , n and some large constant M , our problem is equivalent to the most vital nodes problem for independent set which was studied under the name independence number blocker problem by Diner et al [10]. They left the complexity of this problem as an open question.…”
Section: Interdiction Problemmentioning
confidence: 99%
“…Diner et al [10] proved that the most vital nodes problem for maximum clique size on interval graphs can be solved in O(n) time with a simple greedy algorithm [10]. Note that the most vital nodes problem for maximum clique size is a special case of the interdiction problem for maximum clique size in the shrink-expand framework by setting a i = b i for all i.…”
Section: Interdiction Problemmentioning
confidence: 99%
See 1 more Smart Citation